2021
DOI: 10.3390/ijms22084091
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer Stem Cell Niche in Ovarian Cancer and Its Impact on Immune Surveillance

Abstract: Ovarian cancer is an aggressive gynaecological cancer with extremely poor prognosis, due to late diagnosis as well as the development of chemoresistance after first-line therapy. Research advances have found stem-like cells present in ovarian tumours, which exist in a dynamic niche and persist through therapy. The stem cell niche interacts extensively with the immune and non-immune components of the tumour microenvironment. Significant pathways associated with the cancer stem cell niche have been identified wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 130 publications
(132 reference statements)
0
17
0
Order By: Relevance
“…Most OC patients with recurrence after surgery and first-line chemotherapy are also resistant to second-line chemotherapy, which is a major clinical issue [ 65 , 66 , 67 ]. Growing evidence indicates that the nature of chemoresistance in OC is furthered by the existing subpopulations of drug-resistant OC cells [ 65 , 66 , 68 ]. Our data found that overexpression of several mitotic KIFs manifests a correlation with chemoresistance against drugs currently used in first- and second-line, thereby creating a functional connection between overexpressed mitotic KIFs and drug-resistant OC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most OC patients with recurrence after surgery and first-line chemotherapy are also resistant to second-line chemotherapy, which is a major clinical issue [ 65 , 66 , 67 ]. Growing evidence indicates that the nature of chemoresistance in OC is furthered by the existing subpopulations of drug-resistant OC cells [ 65 , 66 , 68 ]. Our data found that overexpression of several mitotic KIFs manifests a correlation with chemoresistance against drugs currently used in first- and second-line, thereby creating a functional connection between overexpressed mitotic KIFs and drug-resistant OC cells.…”
Section: Discussionmentioning
confidence: 99%
“…These drug-resistant OC cells may be derived from ovarian cancer stem cells (OCSCs), which can undergo genetic or epigenetic changes to generate microenvironmental immunosuppression and intertumoral heterogeneity (ITH) by dynamically interacting with the immunosurveillance and tumor microenvironment [ 68 ]. Most OC patients with tumor-infiltrating lymphocytes (TILs) are supposed to profit from a better outcome [ 68 ]; e.g., it was reported that OC patients whose tumors have intratumoral TILs experienced longer OS and PFS than patients whose tumors lacked TILs [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of the JAK2/STAT3 pathway in OC results in a loss of cancer stemness and reduced tumor growth [ 85 ]. The inhibition of the over-expressed JAK2/STAT3 pathway in patient-derived CD24+ OCSCs correlated with a better survival of OC patients [ 86 ]. The CD24 molecule may also regulate NANOG and OCT4 expression, thus stimulating tumor growth and resistance to chemotherapy.…”
Section: Ovarian Cancer Stem Cells (Ocscs)—markersmentioning
confidence: 99%
“…Thanks to experiments performed recently to shed some light on the role of CSCs. It seems that presence of CSCs in TME results in immune evasion and immunosuppression [ 89 ]. The CSCs are able to induce drug resistance feature of tumor cells.…”
Section: Cancer Stem Cells In Oncologymentioning
confidence: 99%